Implications of climate-smart aquaculture practices on households’ income and food security in Mwanza and Mara, Tanzania’s Lake Zone - Mdoe, Christopher N.; Mahonge, Christopher P; Ngowi, Edwin E. (The North African Journal of Food and Nutrition Research, 2025)
Background: Climate-Smart Aquaculture (CSAq) practices present significant opportunity for the mitigation of climate-related challenges within the aquaculture sub-sector, particularly in the Lake Zone of Tanzania, where aquaculture and fisheries are central to household well-being. Aims: This study aimed to evaluate the impact of three CSAq practices—integrated farming, polyculture, and monoculture—on household income and food security. Methods: A cross-sectional study was conducted between November 2023 and February 2024, involving 384 aquaculture households across the Mara and Mwanza regions. Data were analyzed using descriptive and inferential statistical methods, including chi-square and t-tests, to determine the influence of CSAq practices on economic and food security outcomes. Results: The findings revealed that integrated farming significantly enhanced both household income and food security, with participating households achieving a "Very Satisfactory" Household Food Security Index (HFSI) score. In Mara, where integrated farming was more prevalent, households reported significantly higher yields (3303 ± 155 kg) compared to those in Mwanza (2454 ± 146 kg; t = 4.96, p < 0.001). However, Mwanza exhibited significantly higher prices per kilogram (6719 ± 103 TSH) than Mara (5799 ± 122 TSH; t = -5.29, p < 0.001) attributed to superior market access and infrastructure. Polyculture practices, more frequently adopted in Mwanza (35.7%) than in Mara (21.8%), yielded variable impacts on income and food security. Chi-square analysis (χ² = 9.269, p = 0.010) indicated significant regional disparities in CSAq adoption, with Mara exhibiting higher adoption rates of integrated farming (69.3%) compared to Mwanza (56.0%). Conclusions: This study confirmed that integrated aquaculture-agriculture systems significantly improve household income and food security, while monoculture increases vulnerability. Regional variations indicate higher yields in Mara, associated with the widespread adoption of integrated farming, whereas Mwanza benefited from enhanced market access and elevated fish prices. Strengthening financial access, training programs, and institutional support is crucial for enhancing CSAq adoption. Key recommendations include the expansion of extension services, the improvement of market infrastructure, and the fortification of cooperative support systems to ensure sustainable aquaculture. Keywords: Climate-Smart Aquaculture (CSAq), Income, Food Security, Household Well-being, Tanzania’s Lake Zone.